THE CRITERION OF DISTINGUISHING BETWEEN THE INFRASTRUCTURE AND TRANSPORT ACTIVITIES ON THE RAILWAYS OF UKRAINE - Malakhova, N. B. (Science and Transport Progress, 2006)
The criterion of division of railway transport into two sectors is the peculiarities of the commodity markets, whereon the railway enterprises work. It has been proved that the forms of organization of these two markets for the society are profitable in different ways: the railway infrastructure should be organized as a uniform monopoly enterprise, while the transportation services should be shaped as a set of enterprises, competing among themselves. There has been offered a mechanism of price control of the monopoly enterprise on an equilibrium level of marginal and average costs. An example of average costs calculation has been provided as a base of tariff for a thread of schedule.